2015
DOI: 10.1111/jog.12776
|View full text |Cite
|
Sign up to set email alerts
|

Diathermy versus scalpel in transverse abdominal incision in women undergoing repeated cesarean section: A randomized controlled trial

Abstract: Aim: The aim of this study was to evaluate the volume of blood loss, wound incision time and wound complication according to use of scalpel or electrosurgery during the creation of transverse abdominal incisions during repeated cesarean section (CS). Material and Methods: A randomized controlled trial was carried out at Ain Shams University Maternity Hospital. We recruited 130 women with a history of one previous CS at the time of their planned lower-segment CS. Participants were randomized to anterior abdomin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 35 publications
(47 reference statements)
3
29
1
Order By: Relevance
“…The relation between postoperative wound complications with the methods of diathermy or scalpel being investigated up to date thus conceived analogous results of wound infections that similar to our study (13)(14)(15)(16)(17). Ismail et al have published a systematic review in 2017 December thus included 36 randomized trials, four observational studies, and a quasi-random study, and totally 6422 participants about scalpel and electrocautery comparison.…”
Section: Discussionsupporting
confidence: 81%
“…The relation between postoperative wound complications with the methods of diathermy or scalpel being investigated up to date thus conceived analogous results of wound infections that similar to our study (13)(14)(15)(16)(17). Ismail et al have published a systematic review in 2017 December thus included 36 randomized trials, four observational studies, and a quasi-random study, and totally 6422 participants about scalpel and electrocautery comparison.…”
Section: Discussionsupporting
confidence: 81%
“…Given their scarred uterus, multiparas often face more operative difficulties and require longer surgery times, which may induce more serious noxious stimulation than primary cesarean delivery. 9,10 Moreover, a previous study reported that a history of surgery was associated with a higher risk of inadequate analgesia. 11 In contrast, multiparas that undergo a repeat cesarean delivery are often older, which has been associated with a lower level of postoperative pain.…”
Section: Introductionmentioning
confidence: 99%
“…PO=postoperative; PCIA=patient controlled intravenous analgesia. (11,20) 11 (7,16) Moving incision pain VAS at PO 4h 29 (21,39) 23 (13,30) Visceral pain VAS at PO 4h 22 (6,32) 27 (17,36) Rest incision pain VAS at PO 8h 13 (9,19) 9 (4,13) Moving incision pain VAS at PO 8h 25 (21,34) 22 (12,29) Visceral pain VAS at PO 8h 21 (8,28) 20 (11,30) Rest incision pain VAS at PO 12h 12 (6,15) 9 (3,12) Moving incision pain VAS at PO 12h 24 (21,32) 15 (10,26) Visceral pain VAS at PO 12h 13 (0, 25) 11 (0, 24)…”
Section: Resultsmentioning
confidence: 99%
“…Moving incision pain VAS at PO 48h 20 (12,27) 14 (10,20) Visceral pain VAS at PO 48h 0 (0, 8) 0 (0, 5)…”
Section: Resultsmentioning
confidence: 99%